2014
DOI: 10.1080/02615479.2014.919090
|View full text |Cite
|
Sign up to set email alerts
|

Social Work and Drug Use Teaching: A Personal View from Lancaster University

Abstract: This article offers a personal view about teaching the module 'Social Work and Drug Use' at a university in the North West of England, UK. It describes the establishment of the module and the development of the module content over the years. It discusses the nature of teaching the subject within a research focused establishment and the problems this presents. This is all contextualized within the campaign to have social work and drug use as a compulsory part of the national social work curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The concept of recovery has been subject to much debate (Neale et al, 2015;Neale et al, 2014;Paylor, Measham, & Asher, 2012). In 2008, the UK Drug Policy Commission (UKDPC) 5 convened an expert group to reach consensus on what recovery entailed.…”
Section: The Concept Of Recoverymentioning
confidence: 99%
“…The concept of recovery has been subject to much debate (Neale et al, 2015;Neale et al, 2014;Paylor, Measham, & Asher, 2012). In 2008, the UK Drug Policy Commission (UKDPC) 5 convened an expert group to reach consensus on what recovery entailed.…”
Section: The Concept Of Recoverymentioning
confidence: 99%
“…This is equally applicable to talking about HCV. The lack of guidance exploring the role of social workers in relation to HCV (a notable exception being Paylor, 2009 , 2014 ) may mean that social workers are unsure when to raise the possibility of a test, the kinds of support and information they can provide or how to support people through treatment and beyond (see supplementary data online ).…”
Section: Hepatitis C and Social Workmentioning
confidence: 99%
“…Someone will be willing to do various ways to meet their basic needs, including criminal acts. Paylor and Smith (2010) identified that the main factors that can cause poverty are unemployment, overpopulation, unequal distribution of resources in the global economy, lack of education, and low employment opportunities. The high unemployment rate will affect the crime rate indirectly because, with an increasing population, it will be more difficult for people to find work.…”
Section: Introductionmentioning
confidence: 99%